Simultaneously Dual Modification of Ni‐Rich Layered Oxide Cathode for High‐Energy Lithium‐Ion Batteries. (7th February 2019) - Yang, Huiping; Wu, Hong‐Hui; Ge, Mingyuan; Li, Lingjun; Yuan, Yifei; Yao, Qi; Chen, Jie; Xia, Lingfeng; Zheng, Jiangming; Chen, Zhaoyong; Duan, Junfei; Kisslinger, Kim; et al.
Abstract: A critical challenge in the commercialization of layer‐structured Ni‐rich materials is the fast capacity drop and voltage fading due to the interfacial instability and bulk structural degradation of the cathodes during battery operation. Herein, with the guidance of theoretical calculations of migration energy difference between La and Ti from the surface to the inside of LiNi0.8 Co0.1 Mn0.1 O2, for the first time, Ti‐doped and La4 NiLiO8 ‐coated LiNi0.8 Co0.1 Mn0.1 O2 cathodes are rationally designed and prepared, via a simple and convenient dual‐modification strategy of synchronous synthesis and in situ modification. Impressively, the dual modified materials show remarkably improved electrochemical performance and largely suppressed voltage fading, even under exertive operational conditions at elevated temperature and under extended cutoff voltage. Further studies reveal that the nanoscale structural degradation on material surfaces and the appearance of intergranular cracks associated with the inconsistent evolution of structural degradation at the particle level can be effectively suppressed by the synergetic effect of the conductive La4 NiLiO8 coating layer and the strong TiO bond. The present work demonstrates that our strategy can simultaneously address the two issues with respect to interfacial instability and bulk structural degradation, and it represents a significant progress in the development of advanced cathode materials for high‐performance lithium‐ion batteries. Abstract : Ti‐doped and La4 NiLiO8 ‐coated Ni‐rich layered oxide cathodes are synchronously and in situ synthesized with the guidance of theoretical calculations, which exhibit good surficial stability, fast interfacial kinetic behaviors, suppressed inconsistent structural degradation in combination with markedly improved electrochemical performance. This work opens a new avenue of designing simple modification approaches and advanced cathodes for high‐energy lithium‐ion batteries.